ANALISIS TENTANG FAKTOR YANG MEMPENGARUHI KESADARAN HUKUM MASYARAKAT DI DESA PULAU KIJANG KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI TERHADAP HAK ANAK MENURUT UU NO 35 TAHUN 2014 - Lili Oktavia Ningsih; Sri Erlinda; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Children are trust and the gift of God, have the dignity, the dignity and rights as a human being must be respected. Children are budding, potential and future generations the ideals of the nation. Children are potential and human resources for national development, requiring the construction of protection. Law number 35 of 2014 No. 109, Section 1, Article 1 determines that the child is a person under eighteen (18) years, including a child still in the womb. The life of a child is not free from problems, be it economic, social, education, all of which can not be resolved by the boy's own legal population in this study are all the people in the village of Deer Island by 316 families .. Based on the population above, then according Suharsimi Arikunto when the subject is less than 100, better all samples taken all his research is to study the population, then if a large number of subjects can in ambilantara 10-15% or 20-25% ataulebih. Suharsimi Arikunto. , the sampling technique is purposive sampling, the sample in this study is 10% of the total population that is 316 x 10% .Then obtained sample of 32 families. Data were collected through observation, questionnaires, interviews, and technical literature. In analyzing the data using qualitative descriptive analysis.The results of this study indicate that there is still low awareness of Community law KJV Rights of the Child in the village of Deer Island Hilir Regency Kuantan District Kuantan SINGINGI. Judging from the results of 32 percent of respondents saying. stating YES is 33%. And stating None 67%. It can be concluded that legal awareness in the village of Deer Island Hilir Regency Kuantan District Kuantan Singingi still relatively less well.Key words : Factors Legal Awareness of the Rights of the Child